2018
DOI: 10.1038/s41598-018-23337-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative whole-genome sequence analysis of Mycobacterium tuberculosis isolated from tuberculous meningitis and pulmonary tuberculosis patients

Abstract: Tuberculous meningitis (TBM) is a severe form of tuberculosis with a high mortality rate. The factors associated with TBM pathogenesis are still unclear. Using comparative whole-genome sequence analysis we compared Mycobacterium tuberculosis (Mtb) isolates from cerebrospinal fluid of TBM cases (n = 73) with those from sputum of pulmonary tuberculosis (PulTB) patients (n = 220) from Thailand. The aim of this study was to seek genetic variants of Mtb associated with TBM. Regardless of Mtb lineage, we found 242 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 33 publications
0
23
0
2
Order By: Relevance
“…Nevertheless, we have shown that glibenclamide enhances IL-10 levels in vitro . In Thailand, East Asian (w/Beijing) strains predominated in both TB meningitis and pulmonary TB disease ( 56 ). However, our study used only Mtb H37Rv, the most studied strain of TB in research laboratories ( 57 ), and BCG, with which most Thai people have been vaccinated ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we have shown that glibenclamide enhances IL-10 levels in vitro . In Thailand, East Asian (w/Beijing) strains predominated in both TB meningitis and pulmonary TB disease ( 56 ). However, our study used only Mtb H37Rv, the most studied strain of TB in research laboratories ( 57 ), and BCG, with which most Thai people have been vaccinated ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…The intersecting SNPs were used for further analysis. Criteria for single nucleotide variant filtering was used to meet high-confidence variants, according to the study of Faksri et al 52 ; mapping quality >50, base Genomic sequence data availability. Whole genome sequence data used in this study were deposited at European Nucleotide Archive (ENA) of EMBL-EBI under the accession numbers ERP006738.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of the tuberculosis burden and deaths are concentrated in middle-income countries. There are few studies making attempts to relate extrapulmonary forms of the disease to a specific genetic variant of M. tuberculosis on a genome-wide scale ( 2 4 ). In order to continue efforts to identify a genetic variant that could impact disease severity and tissue tropism, more genome sequences of extrapulmonary strains from different geographic regions need to be analyzed.…”
Section: Genome Announcementmentioning
confidence: 99%